Estimation of anisotropy of mechanical properties in Mg alloys by means of compressive creep tests - Dobes, F.; Perez, P.; Milieka, K.; Garces, G.; Adeva, P. (Проблемы прочности, 2008)
A detailed knowledge of dependence of mechanical properties on orientation in materials prepared by directional processes may present an important factor influencing the design of construction parts. Toward this end, the compressive creep testing of short specimens may be useful. Three different magnesium-based materials were subjected to this testing: (i) pure magnesium, (ii) magnesium matrix composite reinforced with 10 vol.% of titanium, and (iii) magnesium alloy WE54. All three materials were prepared through a powder metallurgical route with final hot extrusion. The specimensfor creep tests were cut in such a way that their longitudinal axis (i.e., the direction of compressive creep stress) and the axis of extruded bar contained a predestined angle. Two extreme cases can be observed: In pure Mg and in Mg-Ti composite, the dependence of the creep rate is very sensitive to the orientation especially at small inclinations from extrusion axis. The greatest creep resistance is observed in specimens with stress axis parallel to the extrusion axis, the lowest at declinationsfrom 45 to 90°. On the other hand, in WE54 no orientation dependence was observed. Possible explanations of the behaviour based on microstructural observations are discussed.